(untitled) (Research, Society and Development, 2021)
Martial arts are considered complete forms of exercise and can contribute to stimulating motor and cognitive skills. The aim of this study was to verify the effectiveness of Wado-ryu Karate-Do training on the cognition of old people diagnosed with mild neurocognitive impairment. Therefore, a clinical trial was carried out with eight people, who responded to a battery of cognitive tests. Data analysis was performed using descriptive and inferential statistics. It was found that in the post-intervention period, the group scored significantly higher on the Digits tasks – forward (p = 0.023), RAVLT A1 to A5 (p = 0.018) and Recognition (p = 0.011), WCST - Conceptual Level Responses (p = 0.020) and Complete Categories (p = .034), Rey’s Complex Figure – delayed recall (p = 0.027) and Spatial Spam forward (p = 0.017) and backward (p = 0.033). In the pre-intervention stage, the group had a longer time to perform the TMT-B task, with a significant reduction (p = 0.012) in their time after the intervention, indicating an improvement in the alternating attention skill. The results suggest that the three-month practice of Wado-ryu Karate-Do is related to a significant improvement in cognition tasks of visual memory, attention, alternate attention, working memory, episodic verbal memory and executive functions.